Off-pump external pericardial patch repair for post-infarct left ventricular free wall rupture: a case series. Issue 3 (15th March 2021) - Mohamed, S; Mazhar, K; Patel, A J; Jeeji, R; Ridley, P; Balacumaraswami, L
Abstract: We describe an off-pump surgical approach to this challenging condition supported by our results from a case series, which would add to existing literature in the management of this life-threatening complication. We identified seven patients who underwent surgical intervention for left ventricular (LV) free wall rupture at our institution. They were all diagnosed to have cardiac tamponade secondary to free wall rupture of the LV in the presence of acute myocardial infarction. The surgical technique comprised of utilizing an external pericardial patch which was secured using surgical biological glues (fibrin-based sealants or gelatin hydrogels). The 30-day mortality, 1-year survival and 2-year survival were 57, 42 and 42%, respectively. Advanced age, female gender and use of cardiopulmonary bypass were characteristics that were not significantly associated with survival. We advocate the use of an off-pump external pericardial patch repair strategy as a 'bridge to recovery' in this extremely high-risk group of patients.